Life Outside the 50-minute Hour: The Personal Lives of Counsellors - Kennedy, Barbara Sampaio Alhanati; Black, Timothy G. (Canadian Journal of Counselling and Psychotherapy, 2010)
This study investigates the effects that becoming and being a professional counsellor, including training and professional practice, can have on one’s personal life. Semi-structured interviews were conducted with six professional counsellors, asking how their training and professional practice has affected their personal lives. Qualitative methodology and thematic analysis were used in this investigation. Findings revealed participants experienced primarily positive effects, which impacted their personal lives in a variety of ways and in a range of areas. It is hoped that this study will inspire future research on how the profession of counselling psychology affects the professionals engaged with this work.